The Relationship Between Entrepreneurs’ Resilient, Emotional Quotient, and Entrepreneurship Leadership for SMEs Business Sustainability: A Conceptual Framework - Haniza, Ahmad; Nazatul Shima, Abdul Rani (AeU, 2015)
This paper aims to present a conceptual framework for small and medium enterprise (SME) business sustainability, where discussion will focus on the entrepreneur’s behavioural side, namely, entrepreneurial resilient, emotional quotients and leadership. The primary objective of this study was to explore the relationship between entrepreneur resilient, emotional quotient, and leadership styles towards business sustainability among SMEs in Malaysia. A review of papers on the three factors, and a conceptual framework are forwarded at the end of this paper.